2021
DOI: 10.1177/1476718x20977583
|View full text |Cite
|
Sign up to set email alerts
|

Parents and children during the COVID-19 quarantine process: Experiences from Turkey and China

Abstract: This paper reports Turkish and Chinese parents’ experiences with their 3–6 year-old children during the COVID-19 quarantine process. Thirteen Turkish and 11 Chinese parents participated in a study that employed semi-structured interviews to examine participant self-perceived experiences. Findings show that the study revealed many commonalities in the experiences of Turkish and Chinese parents with their children during the COVID-19 quarantine process. Cultural differences between parents did not appear to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 59 publications
8
40
1
4
Order By: Relevance
“…It also shows that being isolated, lonely with less interaction may have a different prospect for children. Toran, Sak, Xu, Şahin-Sak and Yu (2021) also affirm our study's findings, where researchers revealed how Turkish and Chinese parents noticed children's changed behavioural characteristics during the quarantine process. The compromised caregiving environment, cold attitude of parents, low warmth, less and unsupportive interaction may aggravate adversity for some children who may show low verbal ability and affect their socio-emotional well-being (Odgers & Jaffee, 2013).…”
Section: The Social Interaction During the Pandemicsupporting
confidence: 91%
See 1 more Smart Citation
“…It also shows that being isolated, lonely with less interaction may have a different prospect for children. Toran, Sak, Xu, Şahin-Sak and Yu (2021) also affirm our study's findings, where researchers revealed how Turkish and Chinese parents noticed children's changed behavioural characteristics during the quarantine process. The compromised caregiving environment, cold attitude of parents, low warmth, less and unsupportive interaction may aggravate adversity for some children who may show low verbal ability and affect their socio-emotional well-being (Odgers & Jaffee, 2013).…”
Section: The Social Interaction During the Pandemicsupporting
confidence: 91%
“…Emerging research also notes that the effect on children's eye vision is the most prominent one during this time (Dong et al, 2020). Another study also identified that three to six-year-old children stayed for a long time with mobile phones and electronic screens during the COVID-19 (Toran et al, 2021). Almost all the participants showed their serious concerns regarding their child's eyes due to these online classes.…”
Section: Remote Learning: An Emerging Concernmentioning
confidence: 93%
“…These results are similar to the study of Livingstone et al ( 2015 ). Furthermore, the literature has determined various demographic factors influential in mediation strategies, including family relationships, siblings, parental employment, family income, school attendance, and cultural background (Toran et al, 2021 ). This study found that the number of siblings also plays an important, influential role in parents’ mediation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…They have become more aggressive and anxious and exhibited more misbehaviour. Negative effects on children of spending lengthy periods looking at TV screens and mobile devices have also emerged (Toran, Sak, Xu, Şahin-Sak, & Yu, 2021). That being said, however, activities conducted by teachers through eba.gov.tr have become very important to young children, and some of them have been effective educationally.…”
Section: Turkey: Policies and Practices Of Ecec During The Covid-19 Pandemicmentioning
confidence: 99%